Anti-oxidant properties of high-density lipoprotein and atherosclerosis - Podrez, Eugene A (2010)
1. High-density lipoprotein (HDL) is one of the major carriers of cholesterol in the blood. It attracts particular attention because, in contrast with other lipoproteins, many physiological functions of HDL influence the cardiovascular system in favourable ways unless HDL is modified pathologically. 2. The best known function of HDL is the capacity to promote cellular cholesterol efflux from peripheral cells and deliver cholesterol to the liver for excretion, thereby playing a key role in reverse cholesterol transport. The functions of HDL that have recently attracted attention include anti-inflammatory and anti-oxidant activities. High anti-oxidant and anti-inflammatory activities of HDL are associated with protection from cardiovascular disease. 3. Atheroprotective activities, as well as a functional deficiency of HDL, ultimately depend on the protein and lipid composition of HDL. Conversely, these activities are compromised in many pathological states associated with inflammation. 4. The focus of the present review is on the anti-oxidant and anti-inflammatory functions of HDL and its individual components in relation to protection from atherosclerosis.